2012
DOI: 10.2174/138945012804545533
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis-Targeting Natural Products for Cancer Prevention and Therapy

Abstract: Mitosis is a complex process resulting in division of a cell into two daughter cells, and its failure often results in the death of the daughter cells (via apoptotic, necrotic, or proliferative/senescent death). Many chemicals that inhibit the mitotic process (anti-mitotic drugs) have proven effective for killing cancer cells in vitro and in clinical settings. Among the most studied anti-mitotic drugs are plant-origin natural products including taxanes (e.g. paclitaxel, docetaxel) and vinca alkaloids (e.g. vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 109 publications
0
29
0
Order By: Relevance
“…Luteolin exhibited antiangiogenesis effect by suppressing vascular endothelial growth factor and matrix metalloproteases and was antimetastasis through inhibition of tumor necrosis factor and interleukin-6 which regulate cell migration and metastasis [39]. Besides exhibiting similar mechanisms of action as flavonoids, alkaloids and saponins may also contribute to antiproliferative effects by inducing cell cancer autophagy and antimultidrug resistance and antimitotic effect [40]. Existing data on concomitant use of antioxidant compounds and chemotherapy showed that antioxidant supplementation led to improvement in treatment outcomes, increased survival times, increased tumor response, and reduced toxicity [41].…”
Section: Resultsmentioning
confidence: 99%
“…Luteolin exhibited antiangiogenesis effect by suppressing vascular endothelial growth factor and matrix metalloproteases and was antimetastasis through inhibition of tumor necrosis factor and interleukin-6 which regulate cell migration and metastasis [39]. Besides exhibiting similar mechanisms of action as flavonoids, alkaloids and saponins may also contribute to antiproliferative effects by inducing cell cancer autophagy and antimultidrug resistance and antimitotic effect [40]. Existing data on concomitant use of antioxidant compounds and chemotherapy showed that antioxidant supplementation led to improvement in treatment outcomes, increased survival times, increased tumor response, and reduced toxicity [41].…”
Section: Resultsmentioning
confidence: 99%
“…Since uncontrolled and rapid cell division is a hallmark of cancer, unraveling the molecular mechanisms underlying mitosis is key to understanding how various natural compounds might function as antimitotic agents [8, 10-12]. Many natural compounds that inhibit the mitotic process (antimitotic drugs) have proven effective for killing cancer cells in vitro, in vivo and in clinical settings [8, 10-12]. Among the most studied antimitotic drugs are natural compounds including taxanes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…taxol, paclitaxel, docetaxel) and vinca alkaloids (e.g. vincristine, vinblastine), whose validated targets are the spindle microtubules, as reviewed elsewhere [8, 13-18]. Natural compounds, including vinca alkaloids, were shown to induce cell cycle arrest in mitosis associated with aberrant mitotic spindles, while colchicine was found to exhibit the activities leading to blocking of mitosis, as indicated in [8, 13, 14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations